Time series smoothing with links of inequality form - Касьянов, В. А.; Шафран, К. (Proceedings of National Aviation University (archive), 2000)
Examined is the problem of simultaneous smoothing of two time series when prior information about links between estimated values is presented by linear inequalities. It is shown that accounting of links of such kind lead to more strict estimations. Linear smoothing algorithm was elaborated. To illustrate the effect of use of this algorithm a numerical example is given